Study on the risk of seepage field of Qiantang River underground space excavated in water-rich rheological rock area - Zhang Tianjiao (Applied Rheology, 2023)
With the rapid development of underwater space construction, the theoretical research is at the initial stage. At present, the theoretical research methods mainly include mirror image method and conformal transformation method. At present, almost all the research objects in analytical research are homogeneous soil layers. However, in practical engineering, soil layers are often distributed in layers. In this study, the seepage field of layered soil layers is analyzed, and the analytical derivation method of seepage field in heterogeneous media based on traditional conformal transformation method is given, which is verified by numerical simulation. The hydraulic head loss of the medium with better permeability in shallow layer is very small, and the streamline is vertically distributed. In the weak interlayer, the hydraulic head loss is huge, and the streamline bends greatly, showing a strong horizontal distribution and converging towards the center. It can provide theoretical basis for the design of water and soil pressure in practical engineering.